Routine Surveillance of Upper Urinary Tract Imaging for Diagnosing Upper Urinary Tract Urothelial Cancer Recurrence in Patients with Nonmuscle Invasive Bladder Cancer - Nobutaka Nishimura; Makito Miyake; Tatsuki Miyamoto; Takuto Shimizu; Tomomi Fujii; Yosuke Morizawa; Shunta Hori; Daisuke Gotoh; Yasushi Nakai; Kazumasa Torimoto; Nobumichi Tanaka; Kiyohide Fujimoto (Advances in Urology)
Background. Although routine surveillance imaging to examine upper urinary tract urothelial cancer recurrence during follow-up of nonmuscle invasive bladder cancer is recommended, its necessity remains invalidated. A single-institute long-term follow-up cohort study to evaluate the clinical impact of routine surveillance imaging and identify risk factors for upper urinary tract urothelial cancer recurrence after nonmuscle invasive bladder cancer treatment was conducted. Methods and Materials. A retrospective chart review of 864 patients with primary nonmuscle invasive bladder cancer who underwent initial transurethral resection of bladder tumor between 1980 and 2020 was conducted. The opportunities to diagnose its recurrence were examined. Moreover, oncological outcomes included upper urinary tract urothelial cancer recurrence-free survival and overall survival. Results. Of 864 patients, 19 (2.2%) experienced upper urinary tract urothelial cancer recurrence. Among 19 patients, recurrence was detected through routine imaging in 12 (63.2%), cystoscopy in 2 (10.5%), urine cytology in 2 (10.5%), and presence of gross hematuria in 1 (5.3%). All patients had high- or highest-risk NMIBC at diagnosis of primary nonmuscle invasive bladder cancer. On multivariate Fine-Gray proportional regression analyses, a tumor size of ≥30 mm and carcinoma in situ were independently associated with short upper urinary tract urothelial cancer recurrence-free survival (P=0.040 and 0.0089, respectively). Conclusion. Most patients experiencing upper urinary tract urothelial cancer recurrence were diagnosed by routine surveillance imaging, suggesting its clinical importance, especially for patients with nonmuscle invasive bladder cancer accompanied by a tumor size of ≥30 mm and carcinoma in situ.